Characterizing the pyroelectric coefficient for macro-fiber composites. (25th September 2018) - Acosta, Krystal L; Wilkie, William K; Inman, Daniel J
Abstract: In this work, the pyroelectric coefficient for macro fiber composites (MFCs) was characterized by first modeling the secondary pyroelectric coefficient using material properties of MFCs, and then experimentally computing the total pyroelectric coefficient using two separate thermal chambers. The computed total secondary pyroelectric coefficient was 29.88 μ C m −2 K −1 . The primary pyroelectric coefficient will be higher due to the primary effect having a more dominate influence in ferroelectric materials. The sum of the primary and secondary effects is the total pyroelectric coefficient. The MFC was tested in thermal chambers at NASA Langley and at University of Michigan where the temperature was ramped to 70 °C, as well as thermally cycled between 40 °C and 100 °C. The P2 MFC type yielded a higher pyroelectric coefficient than the P1 type at about −343 versus −82 μ C m −2 K −1 . The higher the pyroelectric coefficient is, the more energy it produces for given temperature fluctuations with time. This leads to future work in energy harvesting using the pyroelectric effect and further advancing potential novel applications using MFCs.